The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/pits.22766
|View full text |Cite
|
Sign up to set email alerts
|

Does educational stress mediate the relationship between intolerance of uncertainty and academic life satisfaction in teenagers during the COVID‐19 pandemic?

Abstract: The present study aims to investigate the mediator role of educational stress in the relationship between intolerance to uncertainty and academic life satisfaction among teenagers. The sample consisted of 257 female and 202 male high school students with an average age of 16.03 (SD = 1.21) continuing their education in the spring semester of the 2020−2021 academic year in Turkey. The data were collected via an online survey. Analyses revealed that intolerance of uncertainty directly and indirectly via educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 121 publications
0
3
0
Order By: Relevance
“…Education during the pandemic was carried out in an improvised way, causing losses in learning, and it is necessary to restore this damage by offering support to families, adolescents and educators ( 25 ) . A study carried out in Turkey showed that adolescents’ satisfaction with school life was impaired due to the uncertainties they faced during the COVID-19 pandemic associated with high levels of stress ( 26 ) . Responsibility for the education of children initially refers to the family and, in this context, the school predisposes to a teaching-learning environment.…”
Section: Discussionmentioning
confidence: 99%
“…Education during the pandemic was carried out in an improvised way, causing losses in learning, and it is necessary to restore this damage by offering support to families, adolescents and educators ( 25 ) . A study carried out in Turkey showed that adolescents’ satisfaction with school life was impaired due to the uncertainties they faced during the COVID-19 pandemic associated with high levels of stress ( 26 ) . Responsibility for the education of children initially refers to the family and, in this context, the school predisposes to a teaching-learning environment.…”
Section: Discussionmentioning
confidence: 99%
“…A educação durante a pandemia foi realizada de maneira improvisada, ocasionando perdas na aprendizagem, sendo necessário restaurar esses danos oferecendo apoio às famílias, adolescentes e educadores (25) . Estudo realizado na Turquia mostrou que a satisfação em relação à vida escolar dos adolescentes foi prejudicada devido às incertezas que enfrentaram durante a pandemia de COVID-19 associada a elevados níveis de estresse (26) . A responsabilidade pela educação dos filhos remete, inicialmente, à família e, nesse contexto, a escola predispõe a um ambiente de ensino-aprendizagem.…”
Section: Discussionunclassified
“…Several studies have explored the above-mentioned topics in relation to the current pandemic of COVID-19, revealing that academic life satisfaction has been damaged by students' inability to tolerate the uncertainty in reference to COVID-19 [71]. Further, Oral and Karakurt [72] demonstrated that the death of a loved one due to COVID-19 increased the levels of intolerance of uncertainty and decreased university students' hardiness.…”
Section: Relationships Among Academic Self-efficacy Procrastination A...mentioning
confidence: 99%